Березневі статті 1654 р. як етап революції і визвольної війни: інтерпретації вітчизняних дослідників. (Zaporizhzhia Historical Review, 2021)
The article is given sacred to the analysis and clarification of description in Ukrainian historiography of the March articles, positions of state sides which co-ordinated them, and value this documents, for Ukraine. The looks of the brightest representatives of the so-called “populist” and “state” schools of domestic historiography of Michael Grushevskogo and Vyacheslava Lipinskogo and interpretation of events undertake to attention foremost in 1654 by modern historians.